CdS and Cd-Free Buffer Layers on Solution Phase Grown Cu2ZnSn(SxSe1- x)4 :Band Alignments and Electronic Structure Determined with Femtosecond Ultraviolet Photoelectron Spectroscopy. Issue 1638 (13th February 2014) - Haight, Richard; Barkhouse, Aaron; Wang, Wei; Luo, Yu; Shao, Xiaoyan; Mitzi, David B.; Hiroi, Homare; Sugimoto, Hiroki
ABSTRACT: The heterojunctions formed between solution phase grown Cu2 ZnSn(Sx Se1- x )4 (CZTS, Se) and a number of important buffer materials including CdS, ZnS, ZnO, and In2 S3, were studied using femtosecond ultraviolet photoemission spectroscopy (fs-UPS) and photovoltage spectroscopy. With this approach we extract the magnitude and direction of the CZTS, Se band bending, locate the Fermi level within the band gaps of absorber and buffer and measure the absorber/buffer band offsets under flatband conditions. We will also discuss two-color pump/probe experiments in which the band bending in the buffer layer can be independently determined. Finally, studies of the bare CZTS, Se surface will be discussed including our observation of mid-gap Fermi level pinning and its relation to Voc limitations and bulk defects.